2014
DOI: 10.1128/jb.02045-14
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nitrogenase Gene Expression by Transcript Stability in the Cyanobacterium Anabaena variabilis

Abstract: The nitrogenase gene cluster in cyanobacteria has been thought to comprise multiple operons; however, in Anabaena variabilis, the promoter for the first gene in the cluster, nifB1, appeared to be the primary promoter for the entire nif cluster. The structural genes nifHDK1 were the most abundant transcripts; however, their abundance was not controlled by an independent nifH1 promoter, but rather, by RNA processing, which produced a very stable nifH1 transcript and a moderately stable nifD1 transcript. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 55 publications
(85 reference statements)
2
43
2
Order By: Relevance
“…The apparent transcription start sites for nifB1 and nifH1 in A. variabilis are identical to those mapped in Anabaena sp. PCC 7120, and there are weak, heterocyst-specific promoters within the coding regions of nifU1 and nifE1 (7,39,46). However, we found no evidence for a promoter in the 300-bp nifU1-nifH1 intergenic region driving expression of nifH1 (39).…”
contrasting
confidence: 69%
See 4 more Smart Citations
“…The apparent transcription start sites for nifB1 and nifH1 in A. variabilis are identical to those mapped in Anabaena sp. PCC 7120, and there are weak, heterocyst-specific promoters within the coding regions of nifU1 and nifE1 (7,39,46). However, we found no evidence for a promoter in the 300-bp nifU1-nifH1 intergenic region driving expression of nifH1 (39).…”
contrasting
confidence: 69%
“…However, we found no evidence for a promoter in the 300-bp nifU1-nifH1 intergenic region driving expression of nifH1 (39). In contrast, we were able to verify primary transcription start sites upstream of nifB1 and hesA1 that matched the published sequence (7,39,46). Further, we demonstrated that the 5= ends of nifH1 and fdxH1 in the nif1 cluster, as well as the V-nitrogenase genes, vnfH and vnfDG, have processed RNA ends, not primary transcript ends (39,46,47).…”
contrasting
confidence: 60%
See 3 more Smart Citations